2015
DOI: 10.1038/srep07757
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive status of seawater in the northwest Pacific more than one year after the Fukushima nuclear accident

Abstract: To understand the impact of Fukushima Nuclear Accident(FNA), eight cruises were performed from 2011-2014. This paper reports the seawater monitoring results of the third cruise, which was conducted in May-June 2012.The northwest Pacific was clearly influenced even more than one year after FNA. However, compared to the monitoring results of the first and second cruises, which were performed in 2011, the seawater radioactivity of the third cruise decreased greatly. The highest value and the highest average of 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…After the FNPP accident, subsurface intrusion of Fukushima-derived radioactive Cs associated with these mode waters has been reported (Kitamura et al, 2013;Kumamoto et al, 2013Kumamoto et al, , 2014Kaeriyama et al, 2014Kaeriyama et al, , 2016Aoyama et al, 2015b;Men et al, 2015;Yoshida et al, 2015). Kitamura et al (2013), Kumamoto et al (2013Kumamoto et al ( , 2014 reported the subsurface peak of Fukushima-derived radioactive Cs within STMW along 149˚E during December 2011-February 2012, in the subtropical region far south from the FNPP-site and just south of KE.…”
Section: Subsurface Intrusion Of Radioactive Cesium With Mode Watersmentioning
confidence: 99%
See 2 more Smart Citations
“…After the FNPP accident, subsurface intrusion of Fukushima-derived radioactive Cs associated with these mode waters has been reported (Kitamura et al, 2013;Kumamoto et al, 2013Kumamoto et al, , 2014Kaeriyama et al, 2014Kaeriyama et al, , 2016Aoyama et al, 2015b;Men et al, 2015;Yoshida et al, 2015). Kitamura et al (2013), Kumamoto et al (2013Kumamoto et al ( , 2014 reported the subsurface peak of Fukushima-derived radioactive Cs within STMW along 149˚E during December 2011-February 2012, in the subtropical region far south from the FNPP-site and just south of KE.…”
Section: Subsurface Intrusion Of Radioactive Cesium With Mode Watersmentioning
confidence: 99%
“…Men et al . () reported the Fukushima‐derived radioactive Cs (9.7 Bq m −3 of 134 Cs) in STMW at 21˚30'N, 125˚E during May–June 2012. Kaeriyama et al .…”
Section: Subsurface Intrusion Of Radioactive Cesium With Mode Watersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was atmospheric deposition of radiocaesium onto the area south of the KE 17 22 23 . Some papers have reported dispersion of FNPP-derived radiocaesium in subsurface waters south of the KE, but the data are limited spatially and temporally 24 25 26 27 28 29 30 . Our previous study documented southward transport of FNPP-derived radiocaesium as far as 18 °N, 135 °E in subsurface waters by September 2012, 18 months after the FNPP accident 24 .…”
mentioning
confidence: 99%
“…The radioactive fallout from the Fukushima Daiichi nuclear disaster caused by the Great East Japan Earthquake was scattered onto fields over a wide region of northern Japan. Several studies have reported inventory analyses of the released radionuclides (Ochiai et al, 2013;Thakur et al, 2013;Thornton et al, 2013;Inoue et al, 2014;Yamaguchi et al, 2014;Tanaka et al, 2015;Kinouchi et al, 2015;Yu et al, 2015;Men et al, 2015). Radioactive decontamination work is now underway in Fukushima and interim storage facilities to store the contaminated soil, leaves, and debris are currently being planned.…”
Section: Introductionmentioning
confidence: 99%